Severe multifocal alopecia areata − An imaging case report - Correia de Oliveira, Susana; Sousa, Patrícia; Pereira, Cecília; Meireles, Carla (BIRTH AND GROWTH MEDICAL JOURNAL, 2023)
The authors report a severe case of a common disorder in a healthy eight-year-old male child. The boy was observed for asymptomatic hair loss with seven months of evolution that greatly disrupted his life and caused him to wear a hat at all times. Alopecia areata was diagnosed, and the boy underwent four years of multiple treatments before achieving full hair regrowth. It should be noted that alopecia areata can be an early sign of an autoimmune disease that may manifest later with other symptoms.